22q11.2 deletion syndrome and schizophrenia. (30th October 2020) - Qin, Xianzheng; Chen, Jiang; Zhou, Tian
Abstract: 22q11.2 deletion is a common microdeletion that causes an array of developmental defects including 22q11.2 deletion syndrome (22q11DS) or DiGeorge syndrome and velocardiofacial syndrome. About 30% of patients with 22q11.2 deletion develop schizophrenia. Mice with deletion of the ortholog region in mouse chromosome 16qA13 exhibit schizophrenia-like abnormal behaviors. It is suggested that the genes deleted in 22q11DS are involved in the pathogenesis of schizophrenia. Among these genes, COMT, ZDHHC8, DGCR8, and PRODH have been identified as schizophrenia susceptibility genes. And DGCR2 is also found to be associated with schizophrenia. In this review, we focused on these five genes and reviewed their functions in the brain and the potential pathophysiological mechanisms in schizophrenia, which will give us a deeper understanding of the pathology of schizophrenia.